A pragmatic approach to the diagnosis and treatment of mixed features in adults with mood disorders. (3rd January 2017) - McIntyre, Roger S.; Lee, Yena; Mansur, Rodrigo B.
Abstract : Mixed features specifier (MFS) is a new nosological entity defined and operationalized in the Diagnostic and Statistical Manual of Mental Disorders (DSM), 5th Edition. The impetus to introduce the MFS and supplant mixed states was protean, including the lack of ecological validity, high rates of misdiagnosis, and guideline discordant treatment for mixed states. Mixed features specifier identifies a phenotype in psychiatry with greater illness burden, as evidenced by earlier age at onset, higher episode frequency and chronicity, psychiatric and medical comorbidity, suicidality, and suboptimal response to conventional antidepressants. Mixed features in psychiatry have historical, conceptual, and nosological relevance; MFS according to DSM-5, is inherently neo-Kraepelinian insofar as individuals with either Major Depressive Disorder (MDD) or Bipolar Disorder (BD) may be affected by MFS. Clinicians are encouraged to screen all patients presenting with a major depressive episode (or hypomanic episode) for MFS. Although "overlapping symptoms" were excluded from the diagnostic criteria (eg, agitation, anxiety, irritability, insomnia), clinicians are encouraged to probe for these nonspecific symptoms as a possible proxy of co-existing MFS. In addition to conventional antidepressants, second generation antipsychotics and/or conventional mood stabilizers (eg, lithium) may be considered as first-line therapies for individuals with a depressive episode as part of MDD or BD with mixed features.